ANALYSIS OF SMOKED PATIN FISH PRODUCTION IN PROCESSING CENTER OF KOTO MASJID VILLAGE IN XIII KOTO KAMPAR SUBDISTRICT KAMPAR RIAU DISTRICT - Yudhi Afrianto; Liswar Hamid; Rio J.M. Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted in Processing Center of Koto Masjid village XIII Koto Kampar Subdistrict, District of Kampar Riau. This study aims to determine what factors lead to failure to achieve the production target of Processing Center. In Conducting this study the author requires the data or information relating to the matter under investigation. The types and sources of data used in this study are secondary data and primary data. Data analysis used descriptive - quantitative. The survey results revealed that the preparation of the company's production planning just follow the thinkinhg of leader, so that the conditions found in the field are often not in accordance with what is laid down by the leadership. According to the authors the company should make a realistic forecast production plan using Linear Trend. Ineffective control problems, the solution given is to form a unit supervisor. So is the condition of production equipment is still good should be used to the maximum by adding manpower production section. The problem of raw materials that were previously less planning and affected by weather and so that Sentra Pengolahan experiencing the shortage of raw materials supply, the solution given is to increase the number of suppliers and the number of pond from each processor.Keywords: Smoked Patin Fish, Production, Linier Trend.